Corporate Governance for Sustainable Development (ESG) Reporting in Poland - Arkadiusz WEREMCZUK; Mariusz CHĄDRZYŃSKI; Sylwester KOZAK; Kamila BOKSZCZANIN (Communications of International Proceedings, 2025)
The research evaluates the degree of corporate-organ liability which affects management teams and supervisory board members regarding their sustainability (ESG) reporting duties in Poland. The research examines ESG reporting obligations under Polish law through analysis of the 2022 Corporate Sustainability Reporting Directive (CSRD) and the modified Polish Accounting Act. The research uses a doctrinal and comparative legal approach to study EU and Polish legal frameworks and official documents from the European Commission and Polish Ministry of Finance and academic and professional literature from law and economics and sustainability fields. The research shows Poland has established managerial sustainability disclosure accountability through its EU requirement implementation process. The management boards of CSRD entities must create reliable ESG reports which they must publish as part of their management reports before submitting them to statutory auditor assurance. The supervisory boards of companies must continuously oversee reporting activities and provide official statements about ESG report completeness and accuracy. The integration of ESG matters into corporate governance structures demonstrates a wider business strategy evolution which incorporates sustainability principles. The combination of European Sustainability Reporting Standards (ESRS) with mandatory assurance requirements will lead to better non-financial data credibility. The research demonstrates that Polish businesses face multiple obstacles during implementation because only 14% of them fulfill the new requirements which creates substantial legal and reputational risks for non-compliance. The Polish legal framework now explicitly defines ESG reporting duties for managers who must handle sustainability information as part of their fiduciary obligations. The new reporting requirements will create long-term benefits by increasing transparency levels and building stakeholder confidence while promoting sustainable business value development.
Keywords: Corporate governance; ESG reporting; Corporate Sustainability Reporting Directive.